Laserbasierte Verfahren zur Herstellung hochdichter Peptidarrays - Märkle, Frieder (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2014)
In this thesis, different laser based methods to produce high density peptide arrays were developed. They use laser radiation to structure special micro particles with amino acids. The particles are heated and fused to a substrate (Combinatorial Laser Fusing) or they are transferred trough a shock wave to another substrate (Combinatorial Laser Transfer). This way, microarrays with up to 1 million spots per cm² are produced whereas the number of chemical coupling cycles is minimized.